2006
DOI: 10.1007/s00268-005-0092-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Treatment Strategy for Mid‐ and Lower‐Thoracic Esophageal Cancer Recurring Locally in the Lymph Nodes of the Neck

Abstract: The aim of the present study was to assess the outcome of treatment for patients with recurrent mid- and lower-thoracic esophageal cancers in whom recurrence was localized to the lymph nodes of the neck, and to determine the best strategy for further treatment. Between 1989 and 2001, 270 patients with mid- and lower-thoracic esophageal cancer underwent curative esophagectomy; 90 of those patients had a cancer recurrence. Our focus was on lymph node recurrence, especially when the recurrent cancers were localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 12 publications
2
24
0
1
Order By: Relevance
“…Lymph node, distant organ, and local recurrence were observed in 22-67, 31-55, and 3-8% of patients, respectively [3,9,10,[12][13][14][15]. In the present study, we also found that 88.6% of recurrences happen within 2 years of curative esophagectomy.…”
Section: Discussionsupporting
confidence: 65%
“…Lymph node, distant organ, and local recurrence were observed in 22-67, 31-55, and 3-8% of patients, respectively [3,9,10,[12][13][14][15]. In the present study, we also found that 88.6% of recurrences happen within 2 years of curative esophagectomy.…”
Section: Discussionsupporting
confidence: 65%
“…However, our finding provides a new experimental model for studies on self-renewal of esophageal epithelial stem cells. Esophageal squamous cell carcinoma has a poor prognosis because of frequent metastasis to the lymph nodes and lungs (14)(15)(16). There is no radical therapy for patients with metastases.…”
Section: Discussionmentioning
confidence: 99%
“…5 On the other hand, a few patients with recurrence in only the neck lymph nodes, including some of our patients, underwent salvage resection followed by acceptable survival times. 6 We think that the nature of the cancer recurring only in the neck lymph nodes or anterior mediastinal lymph nodes differs from that of other recurrent forms, and this difference makes it more amenable to treatment. 6 In our experience, we have treated anterior mediastinal lymph node recurrence by salvage resection followed by chemoradiotherapy in two patients who survived long term as a result.…”
Section: Discussionmentioning
confidence: 97%
“…6 We think that the nature of the cancer recurring only in the neck lymph nodes or anterior mediastinal lymph nodes differs from that of other recurrent forms, and this difference makes it more amenable to treatment. 6 In our experience, we have treated anterior mediastinal lymph node recurrence by salvage resection followed by chemoradiotherapy in two patients who survived long term as a result. However, this remains a hypothesis to be tested, perhaps by examining the relevant signaling pathways in primary and recurrent cancer cells.…”
Section: Discussionmentioning
confidence: 97%